TASK CENTERED SYSTEM DESIGN PADA PERANCANGAN APLIKASI MOBILE SISTEM INFORMASI AKADEMIK (Studi Kasus: UPTTIK Universitas Siliwangi) - Firdan Gusmara Kusumah (Jurnal Sistem Informasi Kaputama (JSIK), 2022)
This research was conducted to provide a User Interface recommendation on the SIMAK Mobile application. This study entitled "TASK CENTERED SYSTEM DESIGN IN DESIGN OF ACADEMIC INFORMATION SYSTEM MOBILE APPLICATIONS (Case Study: UPTTIK Siliwangi University)", uses the Cognitive walkthrough method to test the results of user interface design. Was retested using the System Usability Scale method. The results of the System Usability Scale test show a score of 88, 75 or in the acceptable category.